Effect of TNF-α-Induced Sclerostin on Osteocytes during Orthodontic Tooth Movement - Fumitoshi Ohori; Hideki Kitaura; Aseel Marahleh; Akiko Kishikawa; Saika Ogawa; Jiawei Qi; Wei-Ren Shen; Takahiro Noguchi; Yasuhiko Nara; Itaru Mizoguchi (Journal of Immunology Research)
Osteocytes are abundant cells in bone, which contribute to bone maintenance. Osteocytes express receptor activator of nuclear factor kappa-B ligand (RANKL) and regulate osteoclast formation. Orthodontic tooth movement (OTM) occurs by osteoclast resorption of alveolar bone. Osteocyte-derived RANKL is critical in bone resorption during OTM. Additionally, tumor necrosis factor-α (TNF-α) is important in osteoclastogenesis during OTM. Sclerostin has been reported to enhance RANKL expression in the MLO-Y4 osteocyte-like cell line. This study investigated the effect of TNF-α on sclerostin expression in osteocytes during OTM. In vitro analysis of primary osteocytes, which were isolated from DMP1-Topaz mice by sorting the Topaz variant of GFP-positive cells, revealed that SOST mRNA expression was increased when osteocytes were cultured with TNF-α and that RANKL mRNA expression was increased when osteocytes were cultured with sclerostin. Moreover, the number of TRAP-positive cells was increased in osteocytes and osteoclast precursors cocultured with sclerostin. In vivo analysis of mouse calvariae that had been subcutaneously injected with phosphate-buffered saline (PBS) or TNF-α revealed that the number of TRAP-positive cells and the percentage of sclerostin-positive osteocytes were higher in the TNF-α group than in the PBS group. Furthermore, the level of SOST mRNA was increased by TNF-α. As an OTM model, a Ni-Ti closed-coil spring connecting the upper incisors and upper-left first molar was placed to move the first molar to the mesial direction in wild-type (WT) mice and TNF receptor 1- and 2-deficient (TNFRsKO) mice. After 6 days of OTM, the percentage of sclerostin-positive osteocytes on the compression side of the first molar in TNFRsKO mice was lower than that in WT mice. In this study, TNF-α increased sclerostin expression in osteocytes, and sclerostin enhanced RANKL expression in osteocytes. Thus, TNF-α may play an important role in sclerostin expression in osteocytes and enhance osteoclast formation during OTM.